The Role of BK Teachers in Increasing Student Learning Responsibility at Budi Satrya Junior High School - Murni Dahlena Nasution; Irwan S; Purbatua Manurung (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Learning responsibility is an important character competency that influences students’ academic success and independence. However, some junior high school students still experience difficulties in managing learning obligations, completing assignments, and maintaining academic discipline. This study aims to analyze the role of Guidance and Counseling (BK) teachers in improving students’ learning responsibility at Budi Satrya Junior High School Medan.This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving BK teachers, students, principals, and homeroom teachers. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model through data condensation, data display, and conclusion verification. Data validity was ensured through triangulation, member checking, and audit trails. The findings indicate that BK teachers play roles as facilitators, motivators, counselors, mediators, and evaluators. BK services implemented through individual counseling, classical guidance, consultation, monitoring, and collaboration with school stakeholders contributed to improving students’ discipline, time management, task completion, and learning awareness. The role of BK teachers significantly supports the development of students’ learning responsibility through systematic services and a humanistic approach. Strengthening sustainable BK programs is essential for developing independent, disciplined, and responsible learners in the context of 21st-century education.